From the aesthetic production to the urban reconstruction of the hip – hop tattoos - Daltro Cardoso Rotta; Carlos Diogo Niemeyer; Eliane Ribeiro pardo; Luiz Carlos Rigo; Tatiana Teixeira Silveira (Journal of Physical Education (Maringá), 2008)
This article aims at distinguishing some body practices in the Hip –Hop movement. It is a way to give another meaning to the hybrid aesthetics. We consider this movement from the point of view of the person, the communication, the consumption, which are the theoretical basis for this analysis. In order to achieve this we used as reference the everyday cultural studies carried out by Certreau (1994): the identity crisis analysis of the post modernism done by Hall (2000); the British Sociology School and the elements of communication that spread through the city life by Canevacci (1993).